Real-Time MRI Monitoring of Liquid Embolic Agent (Onyx) Injection in a Swine Arteriovenous Malformation Model - Zawadzki, Michał; Pinkiewicz, Miłosz; Pinkiewicz, Mateusz; Walecki, Jerzy; Walczak, Piotr; Gołubczyk, Dominika; Sady, Maria; Gajewski, Zdzisław (Brain sciences, 2023)
The paradigm is gradually shifting, with radiosurgery and endovascular embolization being increasingly chosen over surgical resection in the selected cases of brain arteriovenous malformations. Routinely used X-ray monitoring of liquid embolic infusion has very good spatial and temporal resolution but is not without significant drawbacks regarding poor visualization of the complex AVM angioarchitecture, especially after many embolizations in the past and therefore limiting the technical ability of the embocure—total occlusion of the feeding arteries, nidus, and draining veins. The purpose of this study was to evaluate the use of real-time MRI guidance in endovascular embolization with Onyx (instead of X-ray) in a single swine rete mirabile (RM) AVM model in order to provide the scaffolding for the real-time MRI guidance method. Onyx propagation was observed in real-time dynamic GE-EPI scan with initial ipsilateral RM filling followed by main cerebral arterial branch distribution. The relatively bright signal within RM and the brain prior to Onyx injection provided a good background for the dark, low signal of the embolic agent spreading in rete mirabile and brain arteries. X-ray picture confirmed Onyx cast distribution at the end of the procedure. In this initial experience, real-time MRI seems to be a promising method that may significantly improve liquid embolic agent infusion monitoring in the future, although requiring further development before clinical use.